Developing Collaboration-Based Supervision Model to Enhance the Professionalism of Early Childhood Education Teachers - Latiana, Lita; Samsudi, Samsudi; Sugiyo, Sugiyo; Slameto, Slameto (The Journal of Educational Development, 2018)
Early childhood education (PAUD) is an education at the level prior to the primary education that has a very important role in preparing future generations. One of the activities undertaken in an effort to improve the professionalism of early childhood education teachers is supervized by supervisors and principals. However, the academic supervision approach used currently is not in accordance with the needs of the early childhood education teachers. This study aims to (1) describe and analyze the current supervision model in Semarang Municipality; (2) describe and analyze the hypothetical model of collaborative supervision for PAUD teachers. This study uses a modified vrsion of Borg and Gall’s research and development (R & D) approach. The subjects of this research were PAUD supervisor and principal as well as PAUD teacher in Semarang Municipality. Data were drawn using interview techniques, questionnaires, documentation, and forum group discussions (FGD). The data were analyzed using descriptive analysis technique which included an analysis of the experts and practitioners’ validation sheets. The preliminary study yielded a factual model which shows that the supervision carried out by the PAUD supervisor has not been routine; the supervision program that he/she created is still a combination of kindergarten and elementary school programs; there has been no collaboration between supervisor and teacher; the results of the supervision have not been discussed with the teacher; there has been no follow up to the results of supervision. The conceptual model in this study was designed in accordance with the collaborative academic supervision theory that there is an agreement between supervisor and teacher therough which the supervision stages included planning, implementation, evaluation, and follow up. The results of the model development include the addition of the follow-up stage that includes monitoring the results of the supervision and guidance on a regular basis to improve the professionalism of the PAUD teachers.